2015
DOI: 10.1002/mbo3.287
|View full text |Cite
|
Sign up to set email alerts
|

Bypasses in intracellular glucose metabolism in iron‐limited Pseudomonas putida

Abstract: Decreased biomass growth in iron (Fe)‐limited Pseudomonas is generally attributed to downregulated expression of Fe‐requiring proteins accompanied by an increase in siderophore biosynthesis. Here, we applied a stable isotope‐assisted metabolomics approach to explore the underlying carbon metabolism in glucose‐grown Pseudomonas putida KT2440. Compared to Fe‐replete cells, Fe‐limited cells exhibited a sixfold reduction in growth rate but the glucose uptake rate was only halved, implying an imbalance between gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 53 publications
(90 reference statements)
8
97
0
Order By: Relevance
“…Focusing on P. protegens Pf-5 and P. putida KT2440, we employed a kinetic flux profiling approach using [U-13 C 4 ]-succinate to evaluate explicitly the biosynthesis of aromatic AA as a specific toxicological target of glyphosate (Figure 5). In this approach, evaluation of in vivo flux through a metabolic reaction in the pathway was considered on the basis that the flux would be proportional to the level of the reactant metabolite and the labeling kinetics of the product metabolite (Yuan et al, 2008;Sasnow et al, 2016). Kinetic incorporation of the labeled succinate in both species was monitored at both the low-dose and high-dose glyphosate exposures and we found that the labeling kinetics remained the same in the absence and presence of glyphosate (Figure 5).…”
Section: Glyphosate Specifically Targets Aromatic Amino Acid Biosynthmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on P. protegens Pf-5 and P. putida KT2440, we employed a kinetic flux profiling approach using [U-13 C 4 ]-succinate to evaluate explicitly the biosynthesis of aromatic AA as a specific toxicological target of glyphosate (Figure 5). In this approach, evaluation of in vivo flux through a metabolic reaction in the pathway was considered on the basis that the flux would be proportional to the level of the reactant metabolite and the labeling kinetics of the product metabolite (Yuan et al, 2008;Sasnow et al, 2016). Kinetic incorporation of the labeled succinate in both species was monitored at both the low-dose and high-dose glyphosate exposures and we found that the labeling kinetics remained the same in the absence and presence of glyphosate (Figure 5).…”
Section: Glyphosate Specifically Targets Aromatic Amino Acid Biosynthmentioning
confidence: 99%
“…putida KT2440, P. putida S12, and P. protegens Pf-5 were obtained from ATCC (American Type Culture Collection, Manassas, VA); the agricultural soil isolate P. fluorescens (strain RA12) was a gift from Dr. Rania Abou-Kandil (Cornell University). Cell cultures (three biological replicates) were grown at 30 • C in a G24 environmental incubator shaker (New Brunswick Scientific, Edison, NJ) at 220 rpm (Sasnow et al, 2016 was provided as the source of organic carbon. For glyphosate dosage, the succinate-containing growth medium was prepared with different concentrations of glyphosate (0, 0.5, or 5 mM glyphosate).…”
Section: Culturing Conditionsmentioning
confidence: 99%
“…In light of the findings that Δ lasR strains induced low iron responsive genes when grown near the WT but not itself, that Δ lasR pyochelin production was necessary for co-culture interactions that lead to increased pyocyanin and rhlI promoter activity, that citrate sensing and catabolism genes were induced in Δ lasR by the presence of the WT, and the knowledge that numerous microbes, including Pseudomonas putida , secrete citrate and other organic acids when iron limited (49, 50, 63, 64), we measured citrate in the supernatants of WT and Δ lasR LB cultures. Citrate concentrations were significantly higher in WT supernatants ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Iron limitation can reduce the function of pathways that require abundant iron including the TCA cycle (47), and when iron access is low, Pseudomonas spp. release partially oxidized metabolic intermediates that accumulate at iron requiring steps (48, 49). Many other species are known to release partially-oxidized metabolic intermediates upon iron limitation (48, 50-52).…”
Section: Introductionmentioning
confidence: 99%
“…One strategy of many bacteria to overcome this challenge is to excrete self-made peptide-based siderophores (such as pyoverdines) into the environment that bind Fe 3+ with high affinity, and thereby increase its bioavailability (Baune et al, 2017; Cornelis and Andrews, 2010; Salah El Din et al, 1997). A second adaptation of P. putida cells to iron-limitation is a change in the proteomic inventory in order to limit the use of Fe-containing enzymes, exemplified by the switch from the Fe-dependent superoxide dismutase (SOD) to a Mn-dependent isoenzyme or by re-routing of entire metabolic pathways (Kim et al, 1999; Sasnow et al, 2016). In contrast, when Fe bioavailability is high, the production of the bacterioferritins Bfra and Bfrβ is increased to enable intracellular storage and thereby improve cellular fitness under potential future conditions of iron starvation (Chen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%